Doubly reflected BSDEs and epsilon f-Dynkin games: Beyond the right-continuous case - Miryana Grigorova; Peter Imkeller; Marie-Claire Quenez; Youssef Ouknine (Bielefeld University, Center for Mathematical Economics (IMW), 2018)
We formulate a notion of doubly reflected BSDE in the case where the barriers xi and zeta do not satisfy any regularity assumption. Under a technical assumption (a Mokobodzki-type condition), we show existence and uniqueness of the solution. In the case where xi is right upper-semicontinuous and zeta is right lower-semicontinuous, the solution is characterized in terms of the value of a corresponding epsilon f-Dynkin game, i.e. a game problem over stopping times with (non-linear) f-expectation, where f is the driver of the doubly reflected BSDE. In the general case where the barriers do not satisfy any regularity assumptions, the solution of the doubly reflected BSDE is related to the value of "an extension" of the previous non-linear game problem over a larger set of "stopping strategies" than the set of stopping times. This characterization is then used to establish a comparison result and a priori estimates with universal constants.
urn:nbn:de:0070-pub-29304468
Keywords: 330; Doubly reflected BSDEs; backward stochastic differential equations; Dynkin game; saddle points; f-expectation; nonlinear expectation; game option; stopping time; stopping system